Perencanaan dan Pengembangan Potensi Daerah melalui Sosialisasi Sistem Tumpangsari di Kelurahan Kali Baros - Rifqie Mardiansyah Purmadi; Nadya Ramadhanty; Setyardi Pratika Mulya (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Intercropping is an agricultural intensification program initiative aimed at achieving optimum outcomes in development and preserving soil fertility. Intercropping is a farming method by simultaneously planting two or more plants in one field, arranged in tidy rows. This program is conducted to introduce intercropping cultivation techniques, in which 2 or more crop commodities are planted simultaneously and close to the Kali Baros community. This initiative aims to provide information about optimal land use and to increase the importance of land use. Intercropping cultivation is performed as it sees the potential of extensive agricultural land as well as farmers in Kalibaros Kelurahan who continue to plant monoculture. The PKK ladies who attended gave enthusiastic welcome to this socialization activity. Participants can receive the presented material and actively ask questions regarding the topic of agriculture. Key words: farming, Kali Baros Village, intercropping